Age as a Mediator of tDCS Effects on Pain: An Integrative Systematic Review and Meta-Analysis - Saldanha, Júlia Schirmer; Zortea, Maxciel; Torres, Iraci Lucena da Silva; Fregni, Felipe; Caumo, Wolnei (Frontiers in Human Neuroscience, 2020)
The transcranial direct current stimulation (tDCS) is a neuromodulatory technique with the potential to decrease pain scores and to improve chronic pain treatment. Although age is an essential factor that might impact the tDCS effect, most studies are solely conducted in adults. Therefore, the age limitation presents a critical research gap in this field and can be shown by only a handful of studies that have included other age groups. To examine the evidence upon the tDCS effect on pain scores on children, adolescents, or elderly, and indirectly, to infer the age-dependent impact on tDCS effects, we conducted a systematic review and meta-analysis. Methods: A systematic review searching the following databases: PubMed, EMBASE, and Science Direct using the following search terms adapted according to MeSh or Entree: [(“Adolescent” OR “Children” OR “Elderly”) AND (“tDCS”) AND (“Pain” OR “Pain threshold”) AND (“dorsolateral prefrontal cortex” OR “Motor cortex)] up to April 20th, 2020. We retrieved 228 articles, 13 were included in the systematic review, and five studies with elderly subjects that had their outcomes assessed by pain score or pain threshold were included in the meta-analysis. Results: For the analysis of pain score, 96 individuals received active stimulation, and we found a favorable effect for active tDCS to reduce pain score compared to sham (P =0.002). The standardized difference was −0.76 (CI 95% = −1.24 to −0.28). For the pain threshold, analysis showed no significant difference between active and sham tDCS. We reviewed two studies with adolescents: one using anodal tDCS over the prefrontal cortex reported a reduction in pain scores. However, the second study reported an increase in pain sensitivity for the dorsolateral prefrontal cortex (DLPFC) stimulation. Conclusion: Our findings suggest tDCS may reduce pain levels in the elderly group. Nevertheless, the small number of studies included in this review – and the considerable heterogeneity for clinical conditions and protocols of stimulation present – limits the support of tDCS use for pain treatment in elderly people. Larger studies on the tDCS effect on pain are needed to be conducted in elderly and adolescents, also evaluating different montages and electrical current intensity.